Detection of Metallo β-lactamase Class among Carbapenem Resistant Acinetobacter baumannii (CRAB) Isolates in Hilla / Iraq - Rabeea Abdulelah Al-Hindawi (Journal of Global Pharma Technology, 2018)
During the period between April 2016 and January 2017, a total of 1100 clinical specimens (burns, wounds, throat, urine, blood) were collected from two hospitals in Babylon province Al-Hillah Teaching Hospital and Medical City of Mirjan Hospital. All specimens were cultured and 17 Acinetobacter baumannii isolates were obtained from clinical specimens in a percentage of (1.5%) distributed in burn 11 (2.8%), wound 1 (0.6%), throat 1 (2%), urine 3 (0.7%) and blood 1 (0.9%).This study was conducted to determine the presence of carbapenem resistance Acinetobacter baumannii (CRAB) isolates and the prevalence of Ampc gene responsible for carbapenem-resistance among clinical isolates of A. baumannii collected from two hospitals in Hillah City. Isolates were identified according to VITEK2 system and further confirmed using PCR technique depending on housekeeping genes. Antibiotics susceptibility was assayed by using disks diffusion method according to CLSI recommendations and it’s found 8 isolates was carbapenem resistant. The Carbapenem resistance Acinetobacter baumannii (CRAB) isolates were subjected to monoplex PCR targeting ampC gene, PCR experiments showed that seven (87.5%) isolates were harbored ampC gene. These results revealed that CRAB isolates constitute 47% of all A. baumannii that had been isolated from Al-Hillah Teaching Hospital and Medical City of Mirjan Hospital in Babylon province. This underlies the importance of their accurate identifications and reporting to prevent the emergence of complete resistance to the most potent drugs against A. baumannii in Babylon province.  Keywords:  CRAB, A. baumannii, Carbapenem.